Z-shaped polycyclic aromatic hydrocarbons with embedded five-membered rings and their application in organic thin-film transistors - Elbert, Sven; Bolgert, Evelin; Paine, Owen; Ghalami, Farhad; Zhang, Wen-Shan; Zschieschang, Ute; Rominger, Frank; Popp, Dennis; Klauk, Hagen; Elstner, Marcus; Mastalerz, Michael (Organic chemistry frontiers, 2024)
Z-shaped polycyclic hydrocarbons with embedded five-membered rings as well as their diaza-analogues have been synthesized. Soluble congeners were obtained by the introduction of mesityl substituents and studied by cyclo- as well as differential pulse voltammetry revealing an amphoteric redox behavior. Unsubstituted congeners showed close π-stacking in single crystal X-ray diffraction analyses and thus promising characteristics for the application as semiconducting materials in p-channel thin-film transistors (TFTs). The hole transport characteristics of the corresponding devices were investigated by GIWAXS.